2021
DOI: 10.1002/mar.21571
|View full text |Cite
|
Sign up to set email alerts
|

Corporate social responsibility in the luxury sector: The role of moral foundations

Abstract: The academic literature on whether consumers respond positively toward corporate social responsibility (hereafter CSR) initiatives in the luxury sector is limited and contradictory. Our research contributes to this on‐going debate by exploring the role of CSR moral foundations. By differentiating individualizing moral foundations (e.g., justice) from binding moral foundations (e.g., loyalty), our three experiments jointly suggest consumers respond more positive toward CSR guided by binding (vs. individualizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 63 publications
(119 reference statements)
0
12
0
Order By: Relevance
“…Disgust generated by ideational factors can have a similar impact on product experience as physical disgust in consumer choice (Galoni et al, 2020;Guido et al, 2018;Lammers et al, 2019;Meng & Leary, 2021). This may point to a potential mechanism for previously documented effects of moral violations on consumer choice (Collins et al, 2007;Hang et al, 2021;Harrison et al, 2005;Hauser et al, 2013;Luttrell et al, 2021;Ouellet, 2007;Thφgersen, 1999). Further, they extend the range of moral associations that can affect consumer behavior, as well as demonstrating that such effects can occur even for incidental moral associations, rather than central product qualities.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Disgust generated by ideational factors can have a similar impact on product experience as physical disgust in consumer choice (Galoni et al, 2020;Guido et al, 2018;Lammers et al, 2019;Meng & Leary, 2021). This may point to a potential mechanism for previously documented effects of moral violations on consumer choice (Collins et al, 2007;Hang et al, 2021;Harrison et al, 2005;Hauser et al, 2013;Luttrell et al, 2021;Ouellet, 2007;Thφgersen, 1999). Further, they extend the range of moral associations that can affect consumer behavior, as well as demonstrating that such effects can occur even for incidental moral associations, rather than central product qualities.…”
Section: Introductionmentioning
confidence: 81%
“…The findings contribute to the literature by illustrating the impact of moral associations in marketing, and specifically by demonstrating that mere association with objectionable moral views can not only undermine choice behavior but vitiate the consumption experience. Extensive research has focused on the impact of marketing actions on product choice (Collins et al, 2007; Hang et al, 2021; Harrison et al, 2005; Hauser et al, 2013; Luttrell et al, 2021; Ouellet, 2007; Thφgersen, 1999), and has shown that moral associations can affect the judgment of specific experiential attributes such as taste. We extend this literature by suggesting that brand rejection may be accounted for by the inherent nature of the disgust generated by objectionable moral stances, which leads to stimulus rejection (H. A. Chapman et al, 2009; Curtis et al, 2004; Frijda, 2007; Rozin & Fallon, 1987; Rozin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motivations for corporate social responsibility have been much questioned and debated. According to Amatulli et al (2018), engagement in corporate social responsibility is associated with intrinsic motives, whereas Sipilä et al (2022) argue that consumers ascribe extrinsic motives to corporate social responsibility engagement within the luxury industry (Hang et al, 2021).…”
Section: Research Hypotheses and Conceptual Frameworkmentioning
confidence: 99%
“…CSR enhances societal well‐being through the voluntary contribution of corporate resources (Korschun et al, 2014), strengthens firm's reputation and competitive advantage (Miller et al, 2020), increases consumer attitudes (Bartikowski & Berens, 2021; Gilal et al, 2021; Hang et al, 2021), consumer‐firm identification (Deng & Xu, 2017), satisfaction (Ghanbarpour & Gustafsson, 2022), purchase intentions (Amatulli et al, 2021; Bhattacharya et al, 2021), cross‐buying (Oluwatobi et al, 2021), brand loyalty (Park et al, 2017), and product performance evaluations (Chernev & Blair, 2015), and decreases consumers' price sensitivity (Jung et al, 2017). CSR reputation positively relates to firms' perceived trustworthiness (Kim & Park, 2020), benevolence (Bhattacharya et al, 2009), ethicality (Sierra et al, 2017), and altruism (Kwak & Kwon, 2016).…”
Section: Conceptual Developmentmentioning
confidence: 99%